Phase 1 study of PSMA ADC, an antibody‐drug conjugate targeting prostate‐specific membrane antigen, in chemotherapy‐refractory prostate cancer. Issue 6 (20th January 2019) - Petrylak, Daniel P.; Kantoff, Philip; Vogelzang, Nicholas J.; Mega, Anthony; Fleming, Mark T.; Stephenson, Joe J.; Frank, Richard; Shore, Neal D.; Dreicer, Robert; McClay, Edward F.; Berry, William R.; Agarwal, Manish; et al.
Abstract : Background: Prostate‐specific membrane antigen (PSMA) is a well‐characterized target that is overexpressed selectively on prostate cancer cells. PSMA antibody‐drug conjugate (ADC) is a fully human IgG1 monoclonal antibody conjugated to the microtubule disrupting agent monomethyl auristatin E (MMAE), which is designed to specifically bind PSMA‐positive cells, internalize, and then release its cytotoxic payload into the cells. PSMA ADC has demonstrated potent and selective antitumor activity in preclinical models of advanced prostate cancer. A Phase 1 study was conducted to assess the safety, pharmacokinetics, and preliminary antitumor effects of PSMA ADC in subjects with treatment‐refractory prostate cancer. Methods: In this first‐in‐man dose‐escalation study, PSMA ADC was administered by intravenous infusion every three weeks to subjects with progressive metastatic castration‐resistant prostate cancer (mCRPC) who were previously treated with docetaxel chemotherapy. The primary endpoint was to establish a maximum tolerated dose (MTD). The study also examined the pharmacokinetics of the study drug, total antibody, and free MMAE. Antitumor effects were assessed by measuring changes in serum prostate‐specific antigen (PSA), circulating tumor cells (CTCs), and radiologic imaging. Results: Fifty‐two subjects were administered doses ranging from 0.4 to 2.8 mg/kg. Subjects had a median of two prior chemotherapy regimens and prior treatment with abiraterone and/or enzalutamide. Neutropenia and peripheral neuropathy were identified as important first‐cycle and late dose‐limiting toxicities, respectively. The dose of 2.5 mg/kg was determined to be the MTD. Pharmacokinetics were approximately dose‐proportional with minimal drug accumulation. Reductions in PSA and CTCs in subjects treated with doses of ≥1.8 mg/kg were durable and often concurrent. Conclusions: In an extensively pretreated mCRPC population, PSMA ADC demonstrated acceptable toxicity. Antitumor activity was observed over dose ranges up to and including 2.5 mg/kg. The observed anti‐tumor activity supported further evaluation of this novel agent for the treatment of advanced metastatic prostate cancer.